1995
DOI: 10.1016/s0377-1237(17)30984-x
|View full text |Cite
|
Sign up to set email alerts
|

Microsomal and Thyroglobulin Antibodies in Thyroid Disorders

Abstract: Eighty patients with various thyroid disorders and 20 controls were investigated to determine antibodies against thyroglobulin and microsomal antigens by haemagglutination and immunofluorescent techniques. They were also tested for immunoglobulin profile by radial immunodiffusion methods. Patients with Hashimoto's disease, idiopathic hypothyroidism, and Grave's disease showed significant elevations of IgG. None of the patients with toxic nodular goitre or thyroid adenoma showed any thyroid antibodies while 69.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Dham et al , (1995) [23] observed that Anti-TPO positive in 58.3% of primary hypothyroidism and in 70% of primary thyrotoxicosis and in 100% of Hashimoto's disease and the study showed a significant elevation in IgG in Graves' disease.Another study by Sultana et al , (2016) [22] revealed that seropositivity of Anti-TPO in patients with hypothyroidism is about (54.54%) ,while in patients with hyperthyroidism is about ( 53.33% ) and approximately agreed with the current study , also its noticed that prevalence of Anti-TPO ,as well as Anti-TG together, comprise 69.09% in hypothyroidism and 66.66% in hyperthyroidism cases which indicate to high seropositivity when these autoantibodies are elevated together in patients. Swain et al , (2005) [24] observed that Anti-TPO is above 60% in hypothyroidism .…”
Section: Resultsmentioning
confidence: 92%
“…Dham et al , (1995) [23] observed that Anti-TPO positive in 58.3% of primary hypothyroidism and in 70% of primary thyrotoxicosis and in 100% of Hashimoto's disease and the study showed a significant elevation in IgG in Graves' disease.Another study by Sultana et al , (2016) [22] revealed that seropositivity of Anti-TPO in patients with hypothyroidism is about (54.54%) ,while in patients with hyperthyroidism is about ( 53.33% ) and approximately agreed with the current study , also its noticed that prevalence of Anti-TPO ,as well as Anti-TG together, comprise 69.09% in hypothyroidism and 66.66% in hyperthyroidism cases which indicate to high seropositivity when these autoantibodies are elevated together in patients. Swain et al , (2005) [24] observed that Anti-TPO is above 60% in hypothyroidism .…”
Section: Resultsmentioning
confidence: 92%
“…The thyroid scan (technetium-99 m pertechnetate scintigraphy) showed diffuse homogenous intake of technetium-99 m pertechnetate in both thyroid lobes ( Figure 3B ). Anti-microsomal antibody and anti-thyroglobulin antibody may be detected in Graves' disease (anti-microsomal antibody: 69.2%, anti-thyroglobulin antibody: 23–30%) ( 20 ); furthermore, with the results of TBII and the thyroid scan results, we diagnosed our patient as having type 1 amiodarone-induced thyrotoxicosis, a form of iodine-induced hyperthyroidism caused by excessive, uncontrolled biosynthesis of thyroid hormone by autonomously functioning thyroid tissue in response to iodine load, which typically develops in underlying latent Graves' disease ( 21 ). After consultation with the endocrinology department, methimazole (20 mg for 17 days followed by 5 mg/d) was used as treatment to manage excessive thyroid hormone synthesis.…”
Section: Case Reportmentioning
confidence: 99%